INTEGRATED CHARACTER EDUCATION MODEL SEBAGAI ALTERNATIF SOLUSI MENGATASI DEGRADASI MORAL PELAJAR INDONESIA - Prasetiawati Prasetiawati (Universitas Batanghari Jambi, 2018)
Abstract: In the middle of globalization era and today’s modernization, the nation character and moral is one of the main many problems are facing by developing countries included Indonesia. Base on this, today’s social fact showed thadt the moral degradation has happened among Indonesian students. It became irony or our country continuation in the future and made writer interested in constructing all the integrated character education models and their relevance toward the effort that overcome moral degradation of Indonesian students. At the end of this writing is concluded that Integrated Character Education Models become important and relevant to be determined to overcome student moral degradation, it also the effort in creating strong student character to face life cgallenge in the future.Keywords: Integrated Character Education Model, Moral Degradation, Students